Impact of zinc and boron foliar application on fruit yield, nutritional quality and oil content of three pomegranate (Punica granatum L.) cultivars. (9th August 2021) - Maity, Ashis; Gaikwad, Nilesh; Babu, K. Dhinesh; Sarkar, Ananta; Patil, Prakash
Abstract: Pomegranate ( Punica granatum L.) productivity is largely governed by the growing condition and cultivar type. In this context a study was undertaken to find out the effect of zinc (Zn) and boron (B) foliar sprays on fruit yield, quality and seed oil content of three pomegranate cultivars viz. Bhagawa, Mridula and Ganesh. Zinc sulfate (0.30%), boric acid (0.25%) and zinc sulfate (0.30%) + boric acid (0.25%) were sprayed on selected trees thrice; at flower bud initiation, 15 and 45 days after blooming. Results showed that foliar sprays of Zn and B alone or in combination increased their concentration in leaves and consequently increased fruit yield. The effect was more pronounced with B than with Zn. Foliar treatment of these elements also significantly improved micronutrient concentration (Fe, Mn, Zn, Cu and B) in fruit. In addition, foliar fertilization of Zn led to significant improvement in fruit quality comprising of 2.84-8.87% increases in aril per cent, 7.84-10.72% increases in ascorbic acid, 0.71-17.48% increases in total phenol, 23.42-120.48% increases in anthocyanin and 30.73-55.30% increases in non-reducing sugar content, while B application resulted 5.09-16.98% increase in seed oil content. The highest level of seed oil content (29.63%) was recorded in cv. Mridula. In conclusion, foliar sprays of either zinc sulfate (0.30%) or boric acid (0.25%) could enhance the economic yield while zinc sulfate was superior in improving the nutritional quality and boric acid in increasing the seed oil content of pomegranate fruit in semiarid region.